Marco conceptual y estado de la cuestión en el estudio de los préstamos léxicos entre las familias lingüísticas quechua y nihagantsi - Faucet Pareja, Carlos Alberto (2025)
A relevant conceptual framework is presented for the study of lexical borrowing between the native languages of the Americas, and within these parameters, a review of the current state of research on lexical borrowing between the Quechua and Nihagantsi language families is conducted (Nihagantsi, also called “Kampan”, is a branch of the Maipuran family, which in turn belongs to the Arawakan group). These two families have traditional territories that border each other in the Peruvian Andes. By analyzing the literature, a journey is made from the late 19th century to the present, encompassing both marginal comments found in catechetical works and systematic academic studies. Additionally, three specific cases of proposed lexical borrowing between the aforementioned families are explored as instances of the strict application of the previously presented conceptual framework. It is concluded that a number of lexical items have been accumulated as hypotheses, purportedly representing borrowings between the varieties of these families. However, none of these hypotheses have been validated due to the failure to meet one or more of the plausibility conditions outlined in the conceptual framework. Furthermore, contrary to much of the previous literature, it is concluded that there is the possibility of borrowing occurring in both directions.